EDITORIAL (Fiep Bulletin - online, 2013)
This edition of the Bulletin FIEP presents a historical overview of the activities of FIEP as institution in the development of Physical Education and Sport in the Americas, Europe and Oceania. A history conducted by professionals of great technical ability, great will and hope in the work developed are also reminded, since the valuation of their legacies is present today at the National Delegates, and the work developed in their countries. As an institution, this editing shows the creation and development of activities in several countries, bringing with them the memory of his most important works. Today, FIEP lives a moment of new changes, and direct its work increasingly focused on ethics and the principles that determine their actions. Present in more than 120 countries, FIEP is today a multidisciplinary institution, with multiple realities, and adapt their activities to the socio-economic and cultural needs of each region. Encouraging development projects in the area of physical education, their professionals, students, researchers, as well as events and projects that go beyond the academic and organizational, as the Physical Education Teachers Without Borders of FIEP. The 90-year FIEP depict the history of an institution actively working for the development of physical education, and seeks to adapt and innovate to keep track of time. The memory of this history is the memory of the legacy, that their very existence is celebrate.